Agro-Industrial Processing and Agricultural Pricing Under Uncertainty - Gersovitz, Mark (Review of Economic Studies, 1986)
Processing domestically available materials for export has intuitive appeal, e.g. if transport costs are reduced. Uncertainty in the supply of the raw material can be a crucial factor. The theoretical model of this paper shows how to choose the optimal processing capacity and, relatedly, the optimal price to pay producers of the input. Issues include: decision makers' preferences; sources and nature of uncertainty; availability of inputs to produce the raw material; and technology and costs of processing. Econometric estimates of the climate-yield relation are used to simulate these decisions for the case of Senegalese groundnut processing.